OFR-60-83 Improved Ground Control Safety In The Stone, Sand And Gravel Industries - Tuncel M. Yegulalp (The National Institute for Occupational Safety and Health (NIOSH), 1981)
The objective of this study was to categorize mining operations in the stone, and sand and gravel industries into areas of similar ground control functions and define initial factors affecting operational safety in each area, by means of utilizing publicly available data, telephone interviews and on site observations. The findings and recommendations presented in this report are based on the information collected during the two phases of the project. They also contain, in part, the collective qualitative opinion of the operators with respect to government rules and regulations on ground control safety and the implementation of these rules and regulations by government inspectors.